SEXUAL EDUCATION FOR LOVE, PERFORMING IN / BY THE SCRIPTURE OF VARIOUS LANGUAGES: PQP PROJECT - Momesso, Maria Regina [UNESP] (Fundacao Univ Tocantins, 2020)
It starts from the premise that the languages form all that we are, we live and bring us the understanding of the world. Every education goes through by the scrilling(the writing process which occurs through the Reading or the Reading that results from the writing process). Mastering them, it helps and cares about ourselves while subjects as we are, promoting an ethical existence and making up it in a masterpiece. This present paper aims the reflections and discursive practices of literary and cybermedia scrilling whose linguistic education makes that transformation possible, guiding the Young people into subjectivities ways. Those aspects affect the youth in favor of a linguistic and sexual education that promotes the self - care an ethical existence. Based on Focault last studies, this paper points up the methodology and the theoretical reflection named The genealogy of ethics. According to those studies, Focault focused between the subject and the truth realtionships, raising the matter about sexuality as one of its themes approached. The results show toward those practices acting in multiplied roles, maximizing and getting easier the world knowledge and its symbolic signs over the human experiences coping with life's conflicts and matters.
Keywords: Scrilling; Discursive practices; Self-care; Ethical existence